INFECTIOUS SALMON ANEMIA - M. Yu. Shchelkanov; M. A. Shulgina; A. P. Stepan’kov; D. N. Lvov; N. N. Kakareka; A. M. Shestopalov; I. V. Galkina; O. G. Shevchenko (Юг России: экология, развитие)
The aim of this work consists in the analysis of modern scientific conceptions about infectious salmon anemia (ISA) etiologically linked with ISAV (infectious salmon anemia virus) (Orthomyxoviridae, Isavirus). ISA is deadly disease of Salmonidae fishes.Discussion. ISA began to extend actively among salmon breeding farms since the extremity of the XX century and poses nowadays serious threat of fishing industry as there are no not only anti-ISAV chemopreparates and effective vaccines, but also scientifically based ideas of ISAV ecology. In the offered review data on the discovery history, taxonomical status, virion morphology and genome structure as well as ecology of ISAV, clinical features, pathogenesis and laboratory diagnostics, actions in the epizootic foci for the prevention of further distribution and prophylaxis of ISA, arrangement for protection against salmon louses and utilized approaches to anti-ISAV vaccines development are discussed. There is very important that ISAV is capable to be transferred by salmon louses – pelagic crustaceans (Copepoda: Caligidae) that allows to classify ISAV as arbovirus ecological group which are transferred due to biological transmission by arthropods (copepods) to vertebrate animals (salmons). It is the only example known so far when representatives of Crustacea act as a vector for arboviruses.Conclusion. Investigation of ISAV ecology turns into one of "touchstones" allowing to judge technological readiness of mankind to master resources of the World Ocean.